KEPADATAN HUNIAN, VENTILASI DAN PENCAHAYAAN TERHADAP KEJADIAN TB PARU DI WILAYAH KERJA PUSKESMAS BINANGA KABUPATEN MAMUJU SULAWESI BARAT - Dina Mariana; Miftah Chairani H. (Jurnal Kesehatan Manarang, 2017)
The home environment is one of the potential factors in the spread of Pulmonary Tuberculosis incidence. This study aims to analyze the environmental risk factors of the incidence of Pulmonary Tuberculosis in the working area Puskesmas Binanga Mamuju 2016. The study design is a case-control study. Sample size of 93 with a comparison between case and control 1: 2. TB case sample 31 patient and control sample 62 people. TB cases are pulmonary TB patients and controls, not the lungs. The data were collected by interview using questionnaire. Bivariate statistic test using Odds Ratio with α = 0,05. The results showed that residential density (OR 1.969, 95% CI: 0.641 - 6.049), Ventilation (OR 1.492, 95% CI: 0.576-3.863), and Lighting (OR 6.471, 95% CI: 0.795 - 52.6) significant to the incidence of pulmonary TB.